The Efficacy of Early Extracorporeal Shockwave Lithotripsy for the Treatment of Ureteral Stones - Kim, Chang Hee; Shin, Dong Seong; Kim, Tae Beom; Jung, Han (Urology Journal, 2019)
Purpose: To determine the efficacy of early extracorporeal shockwave lithotripsy (e-ESWL) in colic patients with ureteral stones and the patient criteria for the most effective e-ESWL. Materials and Methods: 335 patients who received ESWL due to ureteral stone, were divide in two groups: e-ESWL and d-ESWL by the critical cut-off point. we performed the sensitivity and specificity cut-off analyses to identified the critical cut off point. To assess the difference in the factors affecting ESWL success, univariate and multivariate logistic analyses were implemented with using variables: ESWL success; age; gender; BMI; comorbidity; serum creatinine; stone size; stone location; stone laterality; Hounsfield unit (HU); presence of hydronephrosis; and presence of tissue rim. The subgroup analysis for the screened variables was conducted. Result: Optimal e-ESWL was defined to occur within a 24-hour critical cut-off time. Multivariate regression analysis concluded with screened variables: age, stone size, stone location, and HU, that ESWL success was 1.85-fold higher in the e-ESWL patient group. The subgroup analyses the following conditions: ? 65 years old by 1.784- fold; ?10 mm stone size by 1.866-fold; mid to distal stone location by 2.234-fold; and ? 815 HU by 2.130-fold. When all the conditions were met, the e-ESWL success was 3.22-fold higher. Conclusion: In case of colic due to ureteral stones, the patient is recommended to receive a lithotripsy within the first 24 hours. E-ESWL is recommended especially in patients who are ? 65 years, or with a ureteral stone HU ? 815, sized ? 10 mm, or in a mid to distal location.